Предмет: Математика, автор: aruberdalieva

Помогите пожалуйста!

Приложения:

Ответы

Автор ответа: IrkaShevko
1

Ответ:


Пошаговое объяснение:

1)\dfrac{1}{12} (3a+6+12a-4+6a-12)=\dfrac{1}{12} (21a-10)=\dfrac{1}{12} (-42-10)=-\dfrac{13}{3} =-4\dfrac{1}{3}

2)\dfrac{1}{4} (2b+3+2b-2+3)=\dfrac{1}{4} (4b+4)=b+1=-3+1=-2

3)\dfrac{1}{6} (8a-2-2a-3-1)=\dfrac{1}{6} (6a-6)=a-1=5-1=4


aruberdalieva: Спасибо
Автор ответа: llll0505
1
вот это ответ
Посмотрите
Приложения:

aruberdalieva: Спасибо
Похожие вопросы